SOCIO-PSYCHOLOGICAL ASPECTS OF HUSBANDS’ BELONGING TO FAMILY LIFE IN PSYCHOLOGICAL RESEARCH - Arapbaeva Damegul Kurbanovna; Uxukbayeva Marzhan (Galaxy International Interdisciplinary Research Journal, 2023)
The article analyzes the socio-psychological characteristics of a married couple that influence the process of family adaptation in modern psychology. It is known that psychological adaptation is carried out through the assimilation of norms and values in society. It manifests itself in interaction, including communication with others and in vigorous activity. Adaptation to the family also includes the above components and begins as a process of familiarization with family life and gradual entry into it. This period is considered very difficult, because it is emphasized that it requires not only the restructuring of behavior and activities, but also the re-examination of their need-motivation spheres, a new level of self-awareness, and the formation of new relationships with the social environment.